Study of the modulus of rupture and modulus of elasticity of green wood of local tree species - Nathaniel (2015)
Singapore is well-known for its vision of “City in the Garden”, which it achieves by co-existing building and infrastructure development with extensive urban greenery. A large component of this urban greenery comprises of thousands of urban trees. Mature trees are large living structures that can cause harm and inconvenience to the residents of Singapore upon tree failure. Thus, further research about tree failure is needed. This study focuses on measuring the material properties of greenwood. The modulus of elasticity (MOE) and modulus of rupture (MOR) of four common local tree species in Singapore; Saman samanea (Rain tree), Tabebuia rosea (Trumpet tree), Khaya senegalensis (Khaya), and Peltophorum pterocarpum (Yellow Flame) were measured with comparisons made. Three-point bending test was determined to be the most suitable test to measure the properties. In addition, the samples were taken from the site directly and tested immediately to minimize the loss of moisture content. It was found that among them, Tabubuia rosea was the most brittle and Samanea saman was the most ductile. In terms of highest MOE and MOR, the best performing species was held by Peltophorum pterocarpum as it had the highest MOE and MOR. The worst was held by Samanea saman. Future recommendations are to test more species of trees and increase the sample size to improve the database.